PENANAMAN Rizophora mucronata SEBAGAI KEPEDULIAN LINGKUNGAN PESISIR DI DESA KUALA SAMBOJA, KALIMANTAN TIMUR - Irwan Ramadhan Ritonga; Iwan Suyatna; Ristiana Eryati; Dewi Embong Bulan; Mohammad Sumiran Paputungan; Irma Suryana; Widya Kusumaningrum; Nurfadilah Nurfadilah; Rani Novia; Ahmad Ahmad (Universitas Mataram, 2022)
The condition of the Mahakam Delta area, especially the coastal region of Kuala Samboja, Kutai Kartanegara Regency has been decreased due to coastal abrasion and several human activities. As a result, several ecological and economic functions of the mangrove ecosystem on the coast of Kuala Samboja have been dropped. One of the alternative activities carried out by individuals and groups to protect and improve the coastal environment of Kuala Samboja due to the impact of coastal abrasion and human activities is to plant mangrove seedlings. The purpose of this community service activity was to increase knowledge, awareness and concern by academics and students towards the preservation of the coastal environment in Kutai Kartanegara Regency by planting Rizophora mucronata seeds. The mangrove seedling planting activity was carried out on May 30, 2022 in Kuala Samboja Village, Kutai Kartanegara Regency after the student practical course activities were completed. The method used in this activity is a lecture followed by demonstration activities for planting mangrove seedlings for the participants. The result of this community service activity was the planting of 400 seeds of Rizophora mucronata in areas affected by human exploitation and abrasion in the village of Kuala Samboja. The beach clean-up activities have been carried out by the participants around the planting of mangrove seedlings in order to maintain the cleanliness of the coastal environment by collecting various types of garbage scattered around the beach. Several evaluations of activities from the participants were found from the results of mangrove seedling activities, such as the maintenance process, data collection, and monitoring of mangrove seedlings that may need to be carried out by the participants. Therefore, an evaluation of this activity should be carried out by the activity participants to make the successful planting of mangrove seedlings. In general, the planting of mangrove seedlings may increase the knowledge, awareness and concern of the participants for the mangrove ecosystem in Kuala Samboja village. In addition, the collaboration between lecturers, local government and local communities during the planting of mangrove seedlings on the coast of Kuala Samboja village might preserve the mangrove ecosystem in a sustainable manner.